The Complete photo guide to ribbon crafts - Schmidt, Elaine 1950- (Minneapolis, Minn Creative Pub. International, 2009)
"Techniques and projects in step-by-step format for all kinds of ribbon crafts"--Provided by publisher
Includes bibliographical references (p. 220) and index
1
Keywords: Ribbon work